Assessing Patient Satisfaction for Investigative Services at Public Hospitals to Improve Quality of Services - Sodani, P R; Sharma, Kalpa (National Journal of Community Medicine, 2011)
Objective: The main objective of the paper is to assess the satisfaction level of investigative patients at public health facilities of Madhya Pradesh, a State of India. Methods: Data were collected from investigative patients through structured questionnaires at public health facilities in the sampled eight districts of Madhya Pradesh. Settings: Data were collected from District Hospitals, Civil Hospitals and Community Health Centers of the eight selected districts of Madhya Pradesh. Results: A total of 280 investigative patients were included in the study to know their perceptions about the services at the public health facilities. It was found that most of the respondents belong to rural areas (53.9%) and majority (82.1%) lies within the age group of 16-50. 56.4% were male having low level of literacy. 90% of the respondents who availed ultrasonography services and nearly 70% of the investigative patients who have utilized ECG facility found the problem of overcrowding but found the test facility good. However, 67.3% and 76% of the patients reported that the test facility was good who availed the services of laboratory and X-Ray. More than 80% of the total investigative patients reported the behavior of the technicians as good. Nearly 50% of the respondents who availed the services of laboratory and X-ray, reported that privacy and confidentiality was good whereas rest found it satisfactory.